KOMPETENCJE PROFESJONALNE NAUCZYCIELI JĘZYKÓW OBCYCH Z PERSPEKTYWY PODEJŚCIA LUDYCZNEGO W GLOTTODYDAKTYCE – PROJEKT BADANIA - Surdyk, Augustyn (Neofilolog, 2020)
In the pedagogical and glottodidactic literature numerous publications have been devoted to the competences of the teacher, their roles, functions, ways of working with the learner, teaching strategies, teaching styles, class management styles, and finally, models of teacher education. However, it seems that in the vast majority of these publications the authors concentrated on the so-called hard competences, valuing them more than soft skills , and neglecting, or even marginalising, the range and particular components which possibly play a crucial role in the initiation and development of didactic cooperation between the teacher and the learner. At the same time these soft skills are perhaps able to some extent compensate for what is lacking in the range of the teacher hard competences. This article presents the theoretical background and an outline of a research project concerning FL teacher competences. The glottodidactic process is treated as a kind of game where the most important for the teacher in this ludic approach is ludic competence. The article presents hypotheses and research questions which are to be verified in a research planned for the coming year.